Clinical application of acellular matrix derived from the bubaline diaphragm and caprine rumen for the repair of abdominal wall defects in animals - Harendra S. Rathore; Naveen Kumar; Kiranjeet Singh; Swapan K. Maiti; Sameer Shrivastava; Shivaraju Shivaramu; Sonal Saxena; Ravi K. Agarwal (Syiah Kuala University, 2019)
The abdominal wall hernias resulting due to trauma or other clinical conditions are common in animals. Large hernias required the use of synthetic mesh, which is costly and may result in infection, fistula formation, and pain. Application of biomaterials in hernia repair causes a reduction in pain, reduced recovery time, and rate of recurrence. The study was undertaken to test the acellular bubaline diaphragm matrix (BDiaM) and acellular caprine rumen matrix (CRuM) for the repaired hernia in clinical cases. Fresh bubaline diaphragm and caprine rumen were decellularized using sodium deoxycholate (1% for CRuM and 2% for BDiaM) for 48h. Acellularity was ascertained histologically and by DNA quantification. Histologically, both the matrices showed complete acellularity and orderly arranged collagen fibers after 48 h. The DNA contents were significantly (P0.05) reduced in both the matrices in comparison to the native matrices. The BDiaM and CRuM matrices were applied in eight and nine clinical cases of abdominal wall defects, respectively. Animals with BDiaM and CRuM matrices recovered uneventfully and remained sound at least up to 3 months. Hematological and immunological findings were unremarkable. BDiaM and CRuM matrices showed good results without complications. Keywords:Biocompatibility, Bubaline diaphragm matrix, Caprine rumen matrix, DNA quantification, ELISA, SDS-PAGE